Maturidade de escritório de gerenciamento de projetos: o caso do Ministério Público do Rio Grande do Norte - Brito, Max Leandro de Araujo (2012)
The research aimed to evaluate the level of maturity of the project management office of the Public Ministry of the State of Rio Grande do Norte, on the model PMO Maturity Cube. It was based on a theoretical framework that includes project management, project management office and maturity of the project management office. The research was classified as to the purpose as exploratory and descriptive. According to the methods used was a case study, and how to approach is qualitative and quantitative. The research unit was the prosecutor of the State of Rio Grande do Norte, by two guys who represent all of the participants in the project management office of the institution. These subjects were chosen because they act with the office since the foundation of the same, having the knowledge necessary to deepen the research required, and experience with projects and work experience in the area. Data were collected through an adaptation of the evaluation form for the amplitude corporate developed and presented to the scientific environment for Pinto, Cota and Levin (2010). The results revealed that the level of maturity in the current strategic approach is 77%, and 97% desired; tactical approach in current is 66% and 97% desired, and the current operational approach is 78%, and 100% desired. He pointed out that several factors influence the level of maturity of the project management office of the Public Prosecutor and the recurrent related to information technology, regarding the storage and sharing of information. Concluded that the level of maturity of the project management office of the Public Ministry of the State of Rio Grande do Norte is advanced